2019
DOI: 10.3390/fluids4020101
|View full text |Cite
|
Sign up to set email alerts
|

On Moderate-Rayleigh-Number Convection in an Inclined Porous Layer

Abstract: We investigate the flow structure and dynamics of moderate-Rayleigh-number ( R a ) thermal convection in a two-dimensional inclined porous layer. High-resolution numerical simulations confirm the emergence of O ( 1 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…The dissolution rate, for larger inclinations angles, which is the quantity of interest for predicting the dissolution time of carbon dioxide after injection, is found to be given by the diffusive dissolution rate, F diffusive , for times up to t = 1.5 × 10 5 , in agreement with LSA results. A similar trend was also observed by Wen and Chini, 28,29 for the problem of thermal convection in an inclined porous medium subject to a constant temperature difference. In a quite similar fashion, in their first study, 28 the Nusselt number, Nu, is only weakly dependent on θ for θ < 20 • , although there is a slight increase up to a maximum around θ = 10 • .…”
Section: Results Of the Case With Larger Inclination Anglessupporting
confidence: 84%
See 2 more Smart Citations
“…The dissolution rate, for larger inclinations angles, which is the quantity of interest for predicting the dissolution time of carbon dioxide after injection, is found to be given by the diffusive dissolution rate, F diffusive , for times up to t = 1.5 × 10 5 , in agreement with LSA results. A similar trend was also observed by Wen and Chini, 28,29 for the problem of thermal convection in an inclined porous medium subject to a constant temperature difference. In a quite similar fashion, in their first study, 28 the Nusselt number, Nu, is only weakly dependent on θ for θ < 20 • , although there is a slight increase up to a maximum around θ = 10 • .…”
Section: Results Of the Case With Larger Inclination Anglessupporting
confidence: 84%
“…32 The same qualitative suppression mechanism has been observed on "two-sided" systems in previous works. 28,29 In particular, Wen and Chini 28 also report a dramatic change on the dynamics of the "two-sided" system for angles θ > 30, with the complete breakdown of the columnar flow and transition to a large-scale traveling-wave convective roll state, and significant reduction of the transport.…”
Section: Mixing Length and Area Of The Averaged Transverse Profile As...mentioning
confidence: 99%
See 1 more Smart Citation
“…Even when confined to two-dimensional convection, some aspect ratios (typically those where L is close to being an even integer) will exhibit a classical bifurcation from the basic state to a strongly convecting solution, but others (where L is close to being an odd integer) exhibit a smooth transition to strong convection. Another complicating factor is that the work of Wen and Chini [19] has uncovered subcritical onset of convection.…”
Section: Discussionmentioning
confidence: 99%
“…This is the case of the papers by Barletta and Storesletten [13], Rees and Barletta [14], Barletta and Rees [15], Barletta and Celli [16], Celli and Barletta [17]. Further recent studies have been reported by Rees and Bassom [18] and by Wen and Chini [19]. In the former paper, the boundary layer regime is analysed for a porous medium heated from below through an inclined isothermal boundary with uniform suction.…”
Section: Introductionmentioning
confidence: 92%